The life and work of Martin Stuart ("Marty") Feldstein - Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2014)
Martin Stuart ("Marty") Feldstein, currently George F. Baker Professor of Economics at Harvard University and President Emeritus of the National Bureau of Economic Research, Inc. (NBER), is a renowned American economist who has made important contributions to public finance, macroeconomics, social insurance, health economics, the economics of national security, and many other fields of economics.
Keywords: B31; D14; D22; F21; F32; F52; H20; H55; I13; J65; 330; capital accumulation; capital flows; capital gains; capital mobility; charitable contributions; Council of Economic Advisers; depreciation; Feldstein-Horioka paradox; Feldstein-Horioka puzzle; Harvard University; health economics; health insurance; home bias; inflation; international capital flows; international capital mobility; investment; macroeconomics; Martin Stuart Feldstein; National Bureau of Economic Research; national security; Oxford University; public finance; public pensions; saving; social insurance; social security; taxation; unemployment insurance